2016
DOI: 10.1021/acs.orglett.6b03334
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution Driven Diastereo- and Enantioselective Synthesis of cis-β-Heteroaryl Amino Cycloalkanols by Ruthenium-Catalyzed Asymmetric Transfer Hydrogenation

Abstract: The utility of tethered Ru-TsDPEN catalyst has been demonstrated for the asymmetric transfer hydrogenation of rac-α-heteroaryl amino cycloalkanones to construct biologically important cis-β-heteroaryl amino cycloalkanols with two contiguous chiral centers via dynamic kinetic resolution. The stated (R,R)-Teth-TsDPEN-Ru-catalyzed transformation is carried out under mild conditions using formic acid/triethylamine as a hydrogen source with excellent diastereo- and enantioselectivities. Further, this methodology ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Vyas and Bhanage reported as tereoselective synthesis of 2-heteroaryl cycloalkanolsv ia (R,R)-F-catalyzed DKR-ATH ( Figure 27). [48] The a-(N-heteroaryl)ketones werep repared from the corresponding a-bromoketones 112 and N-heterocycles; 1,2,3-triazol analogs 113 were prepared from terminal acetylenes 111 using ac onvenient one-pot procedure involving click chemistry.R eduction of the benzo-fusedk etones yielded virtually stereopure alcohols 117,a nd their absolutec onfiguration was assigned according to as ingle crystal X-ray diffraction analysiso fa ni ndane-cored example. The reduction of nonbenzo-fused cyclohexanone and suberone derivatives 113 provided the cis products 114 with up to 96 % ee,h owever the reductiono fc yclopentanone derivativey ieldedt he cis product with only 25 % ee.…”
Section: Non-benzofused Carbocyclesmentioning
confidence: 99%
“…Vyas and Bhanage reported as tereoselective synthesis of 2-heteroaryl cycloalkanolsv ia (R,R)-F-catalyzed DKR-ATH ( Figure 27). [48] The a-(N-heteroaryl)ketones werep repared from the corresponding a-bromoketones 112 and N-heterocycles; 1,2,3-triazol analogs 113 were prepared from terminal acetylenes 111 using ac onvenient one-pot procedure involving click chemistry.R eduction of the benzo-fusedk etones yielded virtually stereopure alcohols 117,a nd their absolutec onfiguration was assigned according to as ingle crystal X-ray diffraction analysiso fa ni ndane-cored example. The reduction of nonbenzo-fused cyclohexanone and suberone derivatives 113 provided the cis products 114 with up to 96 % ee,h owever the reductiono fc yclopentanone derivativey ieldedt he cis product with only 25 % ee.…”
Section: Non-benzofused Carbocyclesmentioning
confidence: 99%
“…1-3, 5) as mentioned in Scheme 25. 69 An excellent enantio and diastereo-selectivity along with higher %ee for synthesized compound has been observed with catalyst 5 whereas catalysts 1, 2, and 3 shows lower conversion. From the result obtained, it can be concluded that polar protic solvent shows tendency for higher %ee, however it shows poor dr ratio, further when aprotic solvent is used it indicates higher %ee along with %dr, thus DCM solvent shows excellent result as compared to other solvent.…”
Section: Use Of Derivatized Dpen/deneb Complexed With Ru-chiral Catalyst In Dkr-ath Processmentioning
confidence: 86%
“…An efficient synthetic route for the construction of biologically relevant cis-2-(azaheteroaryl)cycloalkan-1-ols based on the DKR of racemic 2-substituted cycloalkan-1ones via ATH was reported by Bhanage and Vyas in 2016. 39 The reaction, performed in dichloromethane at 27 °C, was best catalyzed by a Ru-(R,R)-TsDPEN tethered complex (R,R)-CAT14 as a catalyst in combination with a HCO 2 H/Et 3 N (5:2) mixture as the hydrogen source to afford -(azaheteroaryl)cycloalkanols containing two adjacent stereocenters. The reaction tolerated a broad substrate scope and gave 59-96% yield, up to 99:1 dr, and 25-99.9% ee depending on the substitution pattern on the azaheteroaryl groups as well as the cycloalkanone ring size (Scheme 26).…”
Section: Scheme 25mentioning
confidence: 99%